Experimental and computational approach of understanding the gas adsorption in amino functionalized interpenetrated metal organic frameworks (MOFs) - Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Journal of Materials Chemistry, 2011)
Two isostructural, three dimensional, interpenetrated, amino (-NH2) functionalized Metal Organic Frameworks [Cd(ANIC)(2)] (Cd-ANIC-1) and [Co(ANIC)(2)] (Co-ANIC-1) with amine-lined pores have been reported. The framework adopts dia topology with interpenetration. Cd-ANIC-1 and Co-ANIC-1 show high CO2 (273 K) and H-2 (77 K) uptake due to the presence of free -NH2 groups and framework interpenetration. The effect of interpenetration and amino functionalization on gas uptake properties of MOFs has been analysed experimentally and computationally, in the isostructural MOFs Cd-ANIC-1 and Co-ANIC-1.

Enhancement of CO2 uptake in iso-reticular Co based zeolitic imidazolate frameworks via metal replacement - Panda, Tamas; Gupta, Krishna M.; Jiang, Jianwen; Banerjee, Rahul (CrystEngComm, 2014)
Three Co based Zeolitic Imidazolate Frameworks (Co-ZIF-68, -69 and -81) which adopt a GME topology with high porosity have been synthesized. These Co-ZIFs show high CO2 (273 K/298 K) uptake compared to their isostructural Zn based analogues, which has been proved experimentally as well as by ab initio calculations.